2021
DOI: 10.1002/alz.12412
|View full text |Cite
|
Sign up to set email alerts
|

The association of motoric cognitive risk with incident dementia and neuroimaging characteristics: The Atherosclerosis Risk in Communities Study

Abstract: Introduction Motoric cognitive risk (MCR), a clinical syndrome characterized by slow gait speed and subjective cognitive complaints, has been associated with dementia risk. The neuropathological features underlying MCR remain poorly understood. Methods The Atherosclerosis Risk in Communities (ARIC) community‐based cohort study classified participants using standardized criteria as MCR+/– and mild cognitive impairment (MCI)+/– at study baseline (2011–2013). We examined the 5‐year dementia risk and baseline brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 46 publications
(96 reference statements)
2
29
0
Order By: Relevance
“…Previous studies found a correlation between gait parameters and amyloid deposition in subcortical and cortical areas, while a recent study did not find an increased amyloid PET SUVr in MCR+ patients [ 21 ]. Here, for the first time, we also compare tau PET SUVr between MCR+ and MCR- patients, finding no differences.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found a correlation between gait parameters and amyloid deposition in subcortical and cortical areas, while a recent study did not find an increased amyloid PET SUVr in MCR+ patients [ 21 ]. Here, for the first time, we also compare tau PET SUVr between MCR+ and MCR- patients, finding no differences.…”
Section: Discussionmentioning
confidence: 99%
“…For cognitively normal individuals, earlier studies have reported significant correlations between slow gait speed and amyloid deposition in the subcortical and cortical areas (Del Campo et al, 2016;Wennberg et al, 2017). However, recent studies did not find increased amyloid deposition in older adults with MCR (Bommarito et al, 2022;Gomez et al, 2022). In this study, for the first time, we compared plasma Aβ42 among older adults with NC, individuals with MCR and those with AD.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies suggested that the pathophysiological mechanisms underlying MCR were probably heterogeneous ( Bommarito et al, 2022 ). Gomez et al (2022) recruited 204 participants with MCR and noted that MCR was associated with prominent white matter abnormalities and frontoparietal atrophy. A cross-sectional study recruited 38 participants with MCR and reported that lacunar infarcts in the frontal lobe were associated with MCR in older adults ( Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association between MCR and WMH was not well documented and there is scope for argument. Gomez et al examined the difference between MCR and mild cognitive impairment (MCI) using neuroimaging data from Atherosclerosis Risk in Communities Study (ARCS) [12] . Both MCR and MCI associated with increased volume of WMH and MCR associated increase in WMH volume was more than double that associated with MCI [12] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between MCR and WMH was inconsistently presented in various studies. One study revealed that MCR was associated with greater volume of WMH and smaller gray matter volumes in the frontoparietal regions [12] . Conversely, another study showed that MCR was not related to the presence of WMH [13] .…”
Section: Introductionmentioning
confidence: 99%